2017
DOI: 10.32677/ijch.2017.v04.i03.006
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in acute diarrhea: A randomized control trial

Abstract: Background: Probiotics have been used for long in the treatment of acute diarrhea although their efficacy has always remains the subject of discussion. Objective: To determine the effect of probiotics in acute diarrhea among the children in rural population. Method: Double-blinded randomized control trial. We included children of age group 6 months - 5 years suffering from acute diarrhea of <48 h and fulfilling the inclusion criteria. All children were given oral rehydration salts (ORS) ad-lib till the reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The mean recovery time in our study in control group was 4.40±1.22 days and in probiotic group was 4.03±0.89 days (p=0.001.) In the study by Kumar et al 7 recovery time was 4.60±0.88 days in intervention group and 5.31±0.98 days in control group which is close to our study. In some studies recovery time was much shortened by using probiotic.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The mean recovery time in our study in control group was 4.40±1.22 days and in probiotic group was 4.03±0.89 days (p=0.001.) In the study by Kumar et al 7 recovery time was 4.60±0.88 days in intervention group and 5.31±0.98 days in control group which is close to our study. In some studies recovery time was much shortened by using probiotic.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study it was revealed that use of probiotic along with standard treatment regimen of acute watery diarrhea reduces duration, frequency and hospital stay in under five children. In a study by kumar et al 7 , in India, probiotic was found effective in reducing duration of diarrhea and frequency of stool. It is assumed that Indian people has high breast-feeding rates like ours and has similar type of bacterial colonization of gut.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation